HBY - Carbone, Claudia (Tidsskriftet Antropologi, 2003)
The Danish net of highways forms an ‘H’ connecting the country north-south and east-west. This is the starting point for a discussion of contemporary urbanism. The article points out that the increasing physical and virtual communication blurs well-known distinctions between centre/ periphery and urban/rural. The majority of planning tendencies aims at recreating and emphasising these distinctions by enhancing the public space of historical city centres and keeping the landscape clear of permanent human activities. The article argues against these tendencies. It refers to the Danish ‘golden age’ painters who successfully tried to construct a national identity in the first half of the 19th century. They did so by sampling parts of the existing cultural landscape and combine them to a slightly enhanced reality in their paintings. The article tries to do the same by combining already existing elements and tendencies to a polemical image of a partly existing reality based on hybrids between the urban and rural.